Burning Planet: The Story of Fire Through Time - Andrew C. Scott (Oxford University Press, 2018)
Raging wildfires have devastated vast areas of California and Australia in recent years, and predictions are that we will see more of the same in coming years as a result of climate change. But this is nothing new. Since the dawn of life on land, large-scale fires have played their part in shaping life on Earth. Andrew C. Scott tells the whole story of fire's impact on our planet's atmosphere, climate, vegetation, ecology, and the evolution of plant and animal life. It has caused mass extinctions, and it has propelled the spread of flowering plants. The exciting evidence we can now draw on has been preserved in fossilized charcoal, found in rocks hundreds of millions of years old, from all over the world. These reveal incredibly fine details of prehistoric plants, and tell us about climates from deep in earth's history. They also give us insight into how early hominids and humans tamed fire and used it. Looking at the impact of wildfires in our own time, Scott also looks forward to how we might better manage them in future, as climate change has an increasing effect on our world.